Postgraduate Topics in Anaesthesia - Kumar Asokan Anil, Mahadevan V; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2011)
The present examination system is entirely different from the past. The long hours of essay writing are replaced by precise short answer questions. You cannot write volumes on a particular topic. The answers have to be precise. The students of anaesthesia are confronted with many avenues of learning which include textbooks, journals, lectures, refresher courses and their own clinical experience. The book represents a set of short answers from the selected questions asked for postgraduate examinations in standard institutions in the last five years. This is not intended to replace the textbooks, but to augment them. The book is meant to help the postgraduates in preparing for the examination and to give them an insight into the art of short note writing and say serve as a quick reference book before the examination.
Keywords: Anesthesiology; Electronic books